2008
DOI: 10.1073/pnas.0711838105
|View full text |Cite
|
Sign up to set email alerts
|

Capsazepine, a synthetic vanilloid that converts the Na,K-ATPase to Na-ATPase

Abstract: Capsazepine (CPZ), a synthetic capsaicin analogue, inhibits ATP hydrolysis by Na,K-ATPase in the presence but not in the absence of K ؉ . Studies with purified membranes revealed that CPZ reduced Na ؉ -dependent phosphorylation by interference with Na ؉ binding from the intracellular side of the membrane. Kinetic analyses showed that CPZ stabilized an enzyme species that constitutively occluded K ؉ . Low-affinity ATP interaction with the enzyme was strongly reduced after CPZ treatment; in contrast, indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Although, as pointed out by a recent review, administration of anxiolytic drugs commonly produces biphasic dose responses independent of the animal model employed (Calabrese 2008), this effect could be reflecting a lack of drug specificity at high concentrations. For example, it has been recently showed that at micromolar range, capsazepine can interfere with a Na,K-ATPase pump (Mahmmoud 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although, as pointed out by a recent review, administration of anxiolytic drugs commonly produces biphasic dose responses independent of the animal model employed (Calabrese 2008), this effect could be reflecting a lack of drug specificity at high concentrations. For example, it has been recently showed that at micromolar range, capsazepine can interfere with a Na,K-ATPase pump (Mahmmoud 2008).…”
Section: Discussionmentioning
confidence: 99%
“…3, showing more than 2-fold activation of ATP hydrolysis after CPS treatment. The ATP activation curves were analyzed by comparing two different fitting procedures, which revealed interesting information (see a similar analysis in the supplemental material provided in Mahmmoud (35). Fitting a Michaelis-Menten equation to the data showed that CPS treatment increases the ATP affinity.…”
Section: Cps Activation Of Serca and The Effect Of Substrates-resultsmentioning
confidence: 99%
“…Based on the structure of capsaicin, capsazepine was developed as a specific TRPV1 antagonist (7). Although the capsacinoids exert their effects through TRPV1 at submicromolar concentrations, at micro-to millimolar concentrations, they seem to have effects beyond TRPV1-dependent actions, such as inhibitory effects on diverse ion channels and transporters (8)(9)(10)(11). However, little has been documented regarding the effects of the capsaicinoids on the airway ion transport via TRPV1-independent mechanisms.…”
mentioning
confidence: 97%